2020
DOI: 10.22541/au.159647051.17812698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-based genotype and ancestry estimation for potential hybrids with mixed-ploidy

Abstract: Non-random mating among individuals can lead to spatial clustering of genetically similar individuals and population stratification. This deviation from panmixia is commonly observed in natural populations. Consequently, individuals can have parentage in single populations or involving hybridization between differentiated populations. Accounting for this mixture and structure is important when mapping the genetics of traits and learning about the formative evolutionary processes that shape genetic variation am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Pure individuals have Q 12 = 0 because their parents contributed the same ancestry to their offspring's genome, whereas F 1 hybrids have Q 12 = 1 because their parents each contributed different ancestries. Further, F 2 hybrids have on average Q 12 = 0.5 because recombination results in a genome consisting of roughly equal parts same‐source and intersource ancestry, and previously published simulations have demonstrated that backcrossed individuals reside on lines drawn between F 1 hybrids ( Q 12 = 1.0; q = 0.5) and parental individuals ( Q 12 = 0; q = 0 or 1) (Lindtke et al, 2014; Shastry et al, 2021). The distinction between F 1 and F 2 hybrids is particularly relevant in the context of postzygotic incompatibilities in F 2 hybrids because they have recombinant genomes (i.e., chromosomes contain ancestry from both parental species), which could impose lower fitness relative to F 1 or parental individuals (Barton, 2001; Dobzhansky, 1970; Maheshwari & Barbash, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure individuals have Q 12 = 0 because their parents contributed the same ancestry to their offspring's genome, whereas F 1 hybrids have Q 12 = 1 because their parents each contributed different ancestries. Further, F 2 hybrids have on average Q 12 = 0.5 because recombination results in a genome consisting of roughly equal parts same‐source and intersource ancestry, and previously published simulations have demonstrated that backcrossed individuals reside on lines drawn between F 1 hybrids ( Q 12 = 1.0; q = 0.5) and parental individuals ( Q 12 = 0; q = 0 or 1) (Lindtke et al, 2014; Shastry et al, 2021). The distinction between F 1 and F 2 hybrids is particularly relevant in the context of postzygotic incompatibilities in F 2 hybrids because they have recombinant genomes (i.e., chromosomes contain ancestry from both parental species), which could impose lower fitness relative to F 1 or parental individuals (Barton, 2001; Dobzhansky, 1970; Maheshwari & Barbash, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…See Figure for estimates of uncertainty. (c) Individual ancestry classes were assigned based on estimates of ancestry coefficients ( q ) and interspecific ancestry ( Q 12 ) generated with entropy (Gompert et al, 2014; Shastry et al, 2021). Pure parental N .…”
Section: Introductionmentioning
confidence: 99%
“…We quantified population structure without a priori sample information using the Bayesian ancestry-based model entropy v1.2 56 , 57 which is based on the correlated allele frequency model of structure 58 . We used entropy to infer the number of k ancestral populations represented by the data and to estimate admixture proportions ( q ) for individuals.…”
Section: Methodsmentioning
confidence: 99%
“…We used the EM acceleration method in EMU, using 10 eigenvectors for optimization (-e 10) with a maximum of 100 optimization iterations and keeping all eigenvectors as output. We then inferred species groups using the model-based genetic clustering program entropy (Gompert et al 2014;Shastry et al 2021). Entropy infers population structure from multilocus SNP data by assigning individuals partially or completely to groups using Bayesian estimation from genotype likelihoods.…”
Section: Species Assignmentmentioning
confidence: 99%